PENGGUNAAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) BERBANTU MEDIA POSTER UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR PKn PADA SISWA KELAS IV SD 2 BAE KUDUS - Sri Hartatik (Universitas PGRI Yogyakarta, 2020)
Abstract This study aims to promote creativity and student learning outcomes 2 Bae fourth grade second semester of academic year 2016/2017 on subjects Civics material Know the State institutions at the central level through a model of Learning Teams Games Tournaments (TGT) Assisted Media Poste r To achieve these objectives, This research was designed in two cycles. The procedure in each cycle includes the stages: 1) planning, 2) implementation, 3) observation, 4) reflection.The effectiveness of actions in each cycle is measured from the results of observations described, interpreted, and then reflected to determine corrective actions in the next cycle.Action research conducted in two cycles obtained results in the first cycle, the creativity observation results reached a score of 3.0 with a value of 75 with enough predicate and on the learning outcomes of 21 students there were already 12 students or 58% achieved the specified completeness while the remaining 9 students or 42% have not yet reached completion. The highest score obtained by students is 100 while the lowest score is 60, the average student learning outcomes are 75. The average increase in learning outcomes in the first cycle is 9.3% of the average pre-cycle achievement. Cycle II data on the results of observations of creativity reached a score of 3.3 with a score of 83 with a good predicate and learning outcomes showed that of 21 students there were 20 students or 95% had achieved predetermined completeness while the remaining 1 child or 5% had not reached completeness. The highest value obtained by students is 100 while the lowest value is 70. The average student learning outcomes are 83. The increase in learning outcomes that occurred in the second cycle is 9.6%Based on the actions taken, it can be concluded that the application of the Teams Games Tournaments (TGT) Learning Model Assisted by Media Posters , can improve the creativity and achievement of fourth grade students of SD 2 Bae in the second semester of 2016/2017 academic year in the subject of Civics Knowing the State Institutions at the Central Level . an increase in student learning creativity will bring influence to the increased achievement of students.Keyword : TGT, creativity, learning outcomes